Well-Posedness of Multipoint Elliptic-Parabolic Differential Problems - Ashyralyev, Allaberen; Gercek, Okan (UNIV PUTRA MALAYSIA PRESS, 2012)
In the present work, we study the multipoint nonlocal boundary value problem for the elliptic-parabolic equation. The well-posedness of this problem in Holder spaces with a weight is established. In applications, the coercivity inequalities for the solutions of the multipoint mixed nonlocal boundary value problems for elliptic-parabolic equations are obtained.
Keywords: Elliptic-parabolic equation; nonlocal boundary value problems; difference scheme; well-posedness; Mathematics